MicroRNA‐455 regulates brown adipogenesis via a novel HIF1an‐AMPK‐PGC1α signaling network. (24th August 2015) - Zhang, Hongbin; Guan, Meiping; Townsend, Kristy L; Huang, Tian Lian; An, Ding; Yan, Xu; Xue, Ruidan; Schulz, Tim J; Winnay, Jonathon; Mori, Marcelo; Hirshman, Michael F; Kristiansen, Karsten; et al.
Abstract Brown adipose tissue (BAT) dissipates chemical energy as heat and can counteract obesity. MicroRNAs are emerging as key regulators in development and disease. Combining microRNA and mRNA microarray profiling followed by bioinformatic analyses, we identified miR‐455 as a new regulator of brown adipogenesis. miR‐455 exhibits a BAT‐specific expression pattern and is induced by cold and the browning inducer BMP7. In vitro gain‐ and loss‐of‐function studies show that miR‐455 regulates brown adipocyte differentiation and thermogenesis. Adipose‐specific miR‐455 transgenic mice display marked browning of subcutaneous white fat upon cold exposure. miR‐455 activates AMPKα1 by targeting HIF1an, and AMPK promotes the brown adipogenic program and mitochondrial biogenesis. Concomitantly, miR‐455 also targets the adipogenic suppressors Runx1t1 and Necdin, initiating adipogenic differentiation. Taken together, the data reveal a novel microRNA‐regulated signaling network that controls brown adipogenesis and may be a potential therapeutic target for human metabolic disorders.